2017
DOI: 10.1111/joms.12253
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Capabilities in MNCs: Knowledge Transformation for Creative Solution Development

Abstract: The management of knowledge across country units is critical to multinational corporations (MNCs). Building on the argument that boundary spanning leads to the development of creative problem solving outcomes, this study advances the concept of MNC knowledge transformation and examines its relationship with solution creativity. Using questionnaire data on 67 problem solving projects, we find that opportunity formation is an underlying mechanism linking MNC knowledge transformation to the development of creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 124 publications
(218 reference statements)
1
63
1
Order By: Relevance
“…We identified that, when spanning internal boundaries in harsh times, technology scouts are more likely to present external solutions as substitutes to internal R&D, while in slack times, technology scouts are more likely to showcase external solutions as complements to internal R&D. In a related vein, we identified that, due to their limited resources, technology scouts in harsh times are likely to emphasize the channelling and transferring of external knowledge into the organization, while we expect them in slack times to focus on the translation and transformation of external knowledge for their internal constituents (Monteiro and Birkinshaw, ). This extends prior work that suggested that value‐adding, boundary‐spanning activities such as transformation allow for establishing common interests and managing tensions across boundaries, which can ultimately improve an organization's competitive advantage, in particular when knowledge at the boundaries is characterized by high novelty (Carlile, ; Mudambi and Swift, ; Tippman et al, ). We reveal that such value‐adding behaviour by technology scouts may, in fact, be affected by performance feedback and is more likely to emerge in slack times.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…We identified that, when spanning internal boundaries in harsh times, technology scouts are more likely to present external solutions as substitutes to internal R&D, while in slack times, technology scouts are more likely to showcase external solutions as complements to internal R&D. In a related vein, we identified that, due to their limited resources, technology scouts in harsh times are likely to emphasize the channelling and transferring of external knowledge into the organization, while we expect them in slack times to focus on the translation and transformation of external knowledge for their internal constituents (Monteiro and Birkinshaw, ). This extends prior work that suggested that value‐adding, boundary‐spanning activities such as transformation allow for establishing common interests and managing tensions across boundaries, which can ultimately improve an organization's competitive advantage, in particular when knowledge at the boundaries is characterized by high novelty (Carlile, ; Mudambi and Swift, ; Tippman et al, ). We reveal that such value‐adding behaviour by technology scouts may, in fact, be affected by performance feedback and is more likely to emerge in slack times.…”
Section: Resultssupporting
confidence: 75%
“…Studying more systematically the boundary‐spanning processes undertaken by technology scouts has also revealed distinct benefits of spanning internal boundaries to connect external knowledge to R&D or business units to make external knowledge available inside the MNC (Monteiro and Birkinshaw, ). This follows the idea that boundary spanners can better manage tensions between separated entities or groups, hence leading to superior outcomes and improved performance (Carlile, ; Mudambi and Swift, ; Schotter and Beamish, ; Tippman et al, ).…”
Section: Theorymentioning
confidence: 97%
“…Tippman et al () further argue that boundary spanning is not just limited to knowledge transfer, but also extends to more demanding tasks of knowledge transformation. They argue that in global organizations, creative and innovative solutions emerge when collaborators engage in collective, repeated, and iterative actions and interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the boundary‐spanning literature argues that the top managers work as conduits of the knowledge they gain from past work experience in other MNEs. Such knowledge and competence help subsidiary managers in opportunity formation which, in turn, helps in the development of creative solutions for the focal subsidiary (Tippmann, Sharkey Scott, & Parker, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%